Prevalensi gangguan tidur pada penderita parkinson di Poli Saraf RSUD Wangaya Denpasar tahun 2017 - I Putu Gede Wikandikta; Dewa Putu Gde Purwa Samatra; Anak Agung Ayu Meidiary (DiscoverSys Inc., 2020)
Background: Parkinson's disease is one of the major causes of disability in the field of neurology and also the disease is chronic progressive. This disease is caused by the lack of dopamine levels in the body, especially the brain. Parkinson's disease affects a small part of the midbrain called susbstantia nigra. Parkinson's disease usually begins between the ages of 50 and 65, affecting about 1% of the entire population. Total cases of deaths from Parkinson's disease in Indonesia are ranked 12th in the world or 5th in Asia, with a prevalence of 1100 deaths in 2002.Aim: This research aimed to know the prevalence of sleep disorders in patients with Parkinson Disease in Neurology Poly of RSUD Wangaya Denpasar.Method: This research was a descriptive observational study with a cross-sectional approach. The subjects was 61 patients diagnosed with Parkinson Disease and did the treatment in Neurology Poly of RSUD Wangaya Denpasar from January 1, 2017, until December 31, 2017. This research is using primary data from the interview.Results and Conclusion: Patients suffered Parkinson’s disease was 45.9% in 61 - 70 age group; 60.7% men; educational background of subjects was 62.3% senior high school; 36.1% private employee; 85.2% subjects had sleep disorders; 54.1% subjects had insomnia; ; 72.1% subjects didn’t have RLS; 82% subjects didn’t have EDS; 91.8% subjects didn’t have Nocturia. Latar Belakang: Penyakit Parkinson adalah salah satu penyebab utama disabilitas di bidang neurologi dan juga penyakit ini bersifat kronik progresif. Penyakit ini disebabkan oleh kurangnya kadar dopamine dalam tubuh khususnya otak. Penyakit Parkinson memengaruhi bagian kecil dari otak tengah yang bernama susbstantia nigra. Penyakit Parkinson biasanya dimulai antara usia 50 dan 65, menyerang sekitar 1 % dari seluruh populasi. Total kasus kematian akibat penyakit Parkinson di Indonesia menempati peringkat ke-12 di dunia atau peringkat ke-5 di Asia, dengan prevalensi mencapai 1100 kematian pada tahun 2002.Tujuan: Penelitian ini bertujuan mengetahui prevalensi munculnya gangguan tidur pada penderita Parkinson di Poli Saraf Rumah Sakit Umum Daerah Wangaya Denpasar tahun 2017.Metode: Penelitian ini merupakan penelitian deskriptif observasional dengan rancangan penelitian cross sectional. Subjek penelitian adalah 61 pasien yang terdiagnosis menderita Parkinson dan melakukan pengobatan di Poli Saraf RSUD Wangaya Denpasar pada rentang waktu 1 Januari 2017 s.d. 31 Desember 2017. Data penelitian adalah data primer yang diperoleh dari wawancara.Hasil dan Kesimpulan: Pasien Parkinson terbanyak yaitu 45,9% berusia 61-70 tahun; 60,7% berjenis kelamin laki-laki; 62,3% memiliki tingkat pendidikan SMA; 36,1% pegawai swasta; 85,2% mengalami gangguan tidur; 54,1% mengalami insomnia; 72,1% tidak mengalami RLS; 82% tidak mengalami EDS; 91,8% tidak mengalami nokturia.